2012
DOI: 10.1007/s00113-011-2151-2
|View full text |Cite
|
Sign up to set email alerts
|

Beschleunigungsverletzung der Halswirbelsäule in Abhängigkeit vom Unfallmechanismus

Abstract: The observed differences in neuro-otological manifestations of whiplash trauma, which occur depending on the trauma mechanism, can be used for differential diagnostic purposes. The whiplash injuries of the cervical spine induced by an axial rotation acceleration showed a prevalence of central vestibular and sensory disturbances, while the whiplash injuries of the cervical spine induced by a linear acceleration showed a prevalence of peripheral vestibular, sensory and vestibulospinal disorders. Our data thus sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Nacci et al ( 79 ) found that in 90 patients affected with balance disorders following whiplash, VNG tests revealed vestibulopathy in 19% of cases. Finally, Geiger and Aliyev ( 80 ) showed that patients submitted to a linear acceleration during the whiplash showed a prevalence of peripheral vestibular, sensory, and vestibulospinal disorders, which is the case of our patients. Those submitted to AR acceleration (absent from our sample) showed a prevalence of central vestibular and sensory disturbances.…”
Section: Discussionsupporting
confidence: 61%
“…Nacci et al ( 79 ) found that in 90 patients affected with balance disorders following whiplash, VNG tests revealed vestibulopathy in 19% of cases. Finally, Geiger and Aliyev ( 80 ) showed that patients submitted to a linear acceleration during the whiplash showed a prevalence of peripheral vestibular, sensory, and vestibulospinal disorders, which is the case of our patients. Those submitted to AR acceleration (absent from our sample) showed a prevalence of central vestibular and sensory disturbances.…”
Section: Discussionsupporting
confidence: 61%
“…25,31,43,112 Further, there is some suggestion that injuries induced by axial rotation versus linear acceleration during the accident may result in different types of neuro-otological injury. 40 Vestibular migraine might also be triggered by the injury associated with traumatic neck pain. 65,72 Conversely, in those who have a primary diagnosis of concussion, associated neck trauma should also be considered as a potential cause of some symptoms.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Anyway, up to date, no study has investigated the quality and readability of online information concerning posterior cruciate ligament (PCL) reconstruction. PCL injuries can be a consequence of sports activities or traffic accidents and have a major impact not only on individual lives but also on society, considering the costs of care and the prolonged loss of productivity [ 17 , 18 ]. PCL reconstruction by tendon grafting can restore physiologic knee function, allowing a return to common daily activities and sports practice and delaying the onset and evolution of knee osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%